2007
DOI: 10.1159/000102906
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal Predictors of Prostate Cancer

Abstract: Introduction: Androgens are necessary for the development and functioning of the prostate gland. The association of serum testosterone and pituitary hormone levels with prostate cancer development is not completely understood. In this clinical study, we evaluated the role of serum testosterone, free testosterone, luteinizing hormone (LH) and follicle-stimulating hormone (FSH) levels in predicting prostate cancer risk in patients who had transrectal ultrasonography-guided prostate biopsy with the suspicion of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 25 publications
2
27
0
1
Order By: Relevance
“…The pineal hormone melatonin (MLT) may also be involved in the molecular interactions in different malignancies including PCa [2,[17][18][19][20][21][22][23] . Studies in LNCaP cell lines in vivo have shown an inhibition of tumor growth by MLT at nM concentrations with decreased expression of cell cycle markers [20] .…”
Section: -Ht and Mlt Do Not Play A Prominent Role In Pca Cell Line Gmentioning
confidence: 99%
“…The pineal hormone melatonin (MLT) may also be involved in the molecular interactions in different malignancies including PCa [2,[17][18][19][20][21][22][23] . Studies in LNCaP cell lines in vivo have shown an inhibition of tumor growth by MLT at nM concentrations with decreased expression of cell cycle markers [20] .…”
Section: -Ht and Mlt Do Not Play A Prominent Role In Pca Cell Line Gmentioning
confidence: 99%
“…The results of studies trying to the assess significance of circulating androgens to the natural history of prostate cancer are controversial and confusing. Pretreatment serum testosterone levels in prostate cancer patients may be lower [1,2] or higher than patients with benign prostate disease [3]. It seems that free testosterone serum levels do not correlate with PSA [1,4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Pretreatment serum testosterone levels in prostate cancer patients may be lower [1,2] or higher than patients with benign prostate disease [3]. It seems that free testosterone serum levels do not correlate with PSA [1,4,5]. Low testosterone serum levels have been shown to predict locally advanced and high grade disease [2,3,[6][7][8][9][10][11]; however, these findings have not been confirmed in other studies [5,12].…”
Section: Introductionmentioning
confidence: 99%
“…Data was analyzed by t test. *P < 0.05, ** P < 0.01, ***P < 0.001 PCa and T supplementation could offer a protective effect in men with a history of PCa [1][2][3][4][5][6][7][8][9].…”
Section: Discussionmentioning
confidence: 99%
“…Recent literature even suggests that men with lower serum T levels are more likely to have PCa. There is also emerging data to suggest that T may even be protective against PCa growth [1][2][3][4][5][6][7][8][9]. Our previous study indicated that physiological normal levels of androgen inhibit the proliferation of PCa cells in vitro, though low levels of androgen are essential for initial growth of PCa cells [10].…”
Section: Introductionmentioning
confidence: 99%